Comarostaphylis arbutoides (Ericaceae) in central and western Mexico - González-Elizondo, Martha; González-Elizondo, M. Socorro; Zamudio, Sergio (Instituto de Ecología, A.C., 2015)
Comarostaphylis arbutoides, previously known from Guerrero, Oaxaca, and Chiapas in Mexico, as well as from Central America, is additionally recorded from Jalisco, Querétaro, and Hidalgo, extending its known distribution area by almost 500 km northwards. The description of the species is broadened to include the morphological variation found in the newly registered populations, and differences fromComarostaphylis lanata and C. sharpii are clarified.